A marginal cost analysis of a Big Brothers Big Sisters of America youth mentoring program: New evidence using statistical analysis. (June 2019) - Alfonso, Y. Natalia; Lindstrom Johnson, Sarah; Cheng, Tina; Jones, Vanya; Ryan, Leticia; Fein, Joel; Bishai, David
Abstract: The objective of this study was to evaluate the cost of serving one additional youth in the Big Brothers Big Sisters of America (BBBS) program. We used a marginal cost approach which offers a significant improvement over previous methods based on average total cost estimates. The data consisted of eight years of monthly records from January 2008 to August 2015 obtained from program administrators at one BBBS site in the Mid-Atlantic. Results show that the BBBS marginal cost to serve one additional youth was $80 per mentor-month of BBBS mentoring (irrespective of program type). The cost to offer services for the average match duration of 19 months per marginal added youth was $1503. The marginal costs per treated program participant in school-based versus community-based programs were $1199 and $3301, respectively. Marginal cost estimates are in the range of youth mentoring programs with significant returns on investment but are substantially higher than prior BBBS unit cost estimates reported using less robust estimation methods. This cost analysis can better inform policy makers and donors on the cost of expanding the scale of local BBBS programs as well as suggest opportunities for cost savings. Highlights: A marginal cost analysis offers significant improvements over previous estimates based on average total cost. Estimates revealed that community-based mentoring was three times costlier than school-based mentoring. While the first month is costlier, each additional month also carries significant costs per participant. These new estimates may help policy makers improve budget and scale up plans and review opportunities for cost savings.